Length-Weight Relationship of Brown Comber, Serranus hepatus, Linnaeus, 1758 from Iskenderun Bay, Northeastern Mediterranean, Turkey - Başusta, Asiye; Başusta, Nuri; Sangun, Levent (Cemal TURAN, 2017)
This study describes the length-weight relationship (LWR) for Serranus hepatus from Iskenderun Bay, Northeastern Mediterranean, Turkey. A total of 202 individuals were caught from Iskenderun Bay, during the 2015-2016 fishing season. The total length ranged from 5.7-9.5 cm and body weight 2.23-12.19 g. Length-weight relationship was found as the W = 0.0172L2.9664 (R2=0.84, F1,200=21.221, P < 0.001) and SEb= 0.091 (t-test: 32.706 p < 0.01). The types of growth were found isometric growth for all indivuduals of S. hepatus.